The Role of an Islamic Forum (Majelis Taklim) Al-Hidayah to Improve Communities’ Religious Comprehension - Savri Yansah; Arwansyah kirin (AJIS: Academic Journal of Islamic Studies, 2023)
The background of this research is the lack of religion understanding and the practice of religious is not perfect enough. This study aims to describe the role of MAJELIS TAKLIM AL-HIDAYAH to increase religious understanding the which is hold every Friday afternoon. This study uses a qualitative approach because the data which is processed and explained by the description. The data is got by observation, interviews, and documentation method. The sources of this data are primary data sources as the results of interviews to the coaches, administrators, and several members of the Al-Hidayah Majelis Taklim, and secondary data sources derived from activity documentation. The research findings are: (1) After Constructing the congregation's faith, Majelis Taklim the member feels that there is increasing of their faith. (2)  Fostering families to realizing a Sakinah family through routine recitation activities every Friday (3) Empowering the poor people by holding compensation activities for orphans every Ramadan month. (4) Improvement of the household economy because the member are pilgrims participating in the recitation and selling something. 5. The forum is a place to study religion that can increase religious understanding. 6. Fostering harmony among the people by Silaturrahim.